2023
DOI: 10.1002/jcu.23439
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the results of hip ultrasonography in 48 666 infants and efficacy studies of conservative treatment

Abstract: Purpose This study aimed to investigate the detection rate of developmental dysplasia of the hip (DDH) by ultrasound. To obtain the distribution characteristics of the different types (I–IV) and the role of ultrasound in the evaluation of infants with DDH (type IIc and above) receiving conservative treatment. Methods A retrospective analysis was performed. The chi‐square test was used for comparisons between count‐data groups. Two‐sided tests were used for all analyses. The results of ultrasound follow‐up afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…They also added that the majority of these patients had type 2a hip which is mostly considered as hip immaturity rather than a true pathology and 1.40% of the hips showed Graf type 2b and above hip findings. He et al 7 reported that DDH more commonly occurs in girls and at left side in their study cohort and these findings are in line with the previous studies 3,4 …”
supporting
confidence: 89%
See 4 more Smart Citations
“…They also added that the majority of these patients had type 2a hip which is mostly considered as hip immaturity rather than a true pathology and 1.40% of the hips showed Graf type 2b and above hip findings. He et al 7 reported that DDH more commonly occurs in girls and at left side in their study cohort and these findings are in line with the previous studies 3,4 …”
supporting
confidence: 89%
“…2 However, it is also reported that at this age group (4-6 months) overdiagnosis with ultrasound for DDH may be as high as 40%. 6 In this issue of Journal of Clinical Ultrasound: Sonography and Other Imaging Techniques, He et al 7 published a study in which they retrospectively analyzed the sonographic findings of infants examined for DDH screening. The fact that they included a high number of cases (97 332 hips of 48 666 infants) in the study stands out as one of the main strengths of the study.…”
mentioning
confidence: 99%
See 3 more Smart Citations